Effects of roasted soy nut and textured soy protein on the features of metabolic syndrome among elderly women in Babol, Iran - Bakhtiary, Afsaneh (2012)
Metabolic syndrome (MetS) consists of a constellation of factors that raise the risk for cardiovascular diseases (CVD) especially in elderly women. Owing to the complex pathophysiology and phenotypic expressions of MetS, diet is crucial as it is able to positively and simultaneously influence almost all components of the syndrome. As a plant-derived estrogen, soy can be useful in preventing CVD. Thus, this study was undertaken to determine the effects of roasted soy-nut and textured soy protein (TSP) on anthropometric measurements, blood pressure (BP), lipid profile and markers of glucose intolerance, as well as inflammatory and oxidative stress of elderly women aged 60-70 years with MetS in Babol, Iran. This study involved a 12-week Randomized Clinical Trial (RCT). A total of 75 elderly women with MetS, who met the selection criteria, were randomized into three groups, namely, roasted soy-nut (n=25), TSP (n=25) and control (n=25) groups. During the intervention period, the treatment groups consumed 35gm of roasted soy-nut or TSP ona daily basis. All the participants completed the entire study. Both the roasted soy-nut and TSP were well tolerated. Meanwhile, only five participants complained of feeling bloated when they consumed TSP. Anthropometric measurements, which included weight, Body Mass Index (BMI), Waist Circumference (WC), Hip Circumference (HC), Triceps Skin Fold (TSF) thickness, Blood Pressure (BP), physical activity level and dietary intake, were measured at baseline and also every month during the intervention period. The metabolic biomarkers, which included lipid profiles [Triglyceride (TG), Total Cholesterol (TC),High Density Lipoprotein Cholesterol (HDL-C), Low Density Lipoprotein Cholesterol (LDL-C), Very Low Density Lipoprotein Cholesterol (VLDL-C)], Apolipoprotein AI(Apo AI), Apolipoprotein B100 (Apo B100), glucose intolerance markers [Fasting Blood Glucose (FBG), fasting insulin, HOMA-IR, TG/HDL-C], inflammatory and prothrombotic markers [C-Reactive Protein (CRP), fibrinogen], oxidative stress markers [Malondialdehide (MDA), Total Antioxidant Capacity (TAC)] and serum isoflavone daidzein, were measured at baseline and also at the end of the study. In addition, demographic information was collected at baseline through a face -to -face interview. There were no significant differences in the demographic characteristics, anthropometric measurements, BP and metabolic biomarkers of the participants atbaseline. Due to the inclusion of 35-gm/day roasted soy-nut, the value of TSF increased significantly comared to the control group. Other anthropometric variables showed no significant changes in the treatment and control groups. After intervention, the roasted soy-nut showed significantly improved LDL-C, VLDLC and Apo B100 (p<0.05), while those on TSP showed slight significant improvement, compared to the mean changes from the baseline (p<0.001). Similar result was found for Apo AI in both groups (p<0.01). In other words, the value of the change for AI in the treatment groups was significantly greater than that of the control group. Meanwhile, serum TC was significantly decreased in the treatment groups as compared with the control group (p<0.001). Similarly, the consumption of the roasted soy-nut significantly improved FBG, insulin and HOMA-IR after the intervention (p<0.05), while the consumption of TSP showed a significant decrease only in serum insulin as compared to that of the control group (p<0.05). There were also significant differences in the mean changes of FBG, insulin, HOMA-IR and TG/HDL-C ratio in the treatment groups compared to the control group (p<0.001). The results also revealed that after consuming roasted soy-nut and TSP, the value of MDA was significantly lower, whereas more TAC was detected in the roasted soy-nut (p<0.001) and the TSP (p<0.01) groups compared to those of the control group. The comparison of the two treatment groups showed that the mean changes for FBG, insulin and HOMA-IR levels in the roasted soy-nut group were significantly higher than that of the TSP group (p<0.01), while the differences between the two groups were not significant for the lipid profiles and oxidative stress markers. Similarly, the differences in TG, HDL-C, fibrinogen, CRP and BP compared to the control group were also not significant. In conclusion, short-term intakes of roasted soy-nut and TSP have shown to improve the lipid profiles, markers of glucose intolerance and oxidative stress, although the roasted soy-nut contributed more effective than the TSP. Therefore, a moderate daily intake of roasted soy-nut as snacks or TSP as a meal complement may be a safe and a practical modality to reduce or prevent MetS complications among high risk individuals, especially elderly women.